Strategies of Micro, Small, And Medium Enterprises To Be Able To Compete In The International Market - Lely Ika Cahyani; Susilo Toto Raharjo (Return : Study of Management, Economic and Bussines, 2023)
The development of the number of MSMEs that continue to increase every year is not directly proportional to the contribution of the country's export value. One of the low contributions of export value is influenced by MSMEs which are still having difficulty starting market expansion abroad. The purpose of this study is to find out the strategy of MSMEs to be able to internationalize and be able to compete abroad. This study uses qualitative methods using a phenomenological approach. Qualitative data was obtained through in-depth interviews with 3 MSMEs in Central Java that have successfully exported. The results showed that various things can affect the three MSMEs, namely by overcoming export barriers, receiving leverage from the government, and having competitive advantages to be able to successfully export and survive in the international market.